Analisis Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Unit Rawat Inap Rumah Sakit Ibu Dan Anak Setya Bakti Tahun 2022 - Riani Angelica; Cici Demiyati (Jurnal Ilmu Kesehatan dan Gizi, 2023)
The health industry in the Depo City area experiences continuous development from year to year, this causes competition to maintain and increase patient trust to become increasingly difficult. Setya Bakti Mother and Child Hospital as one of the industries engaged in health services feels the impact of competition in the health service industry. Retaining patients is the main thing that must be done. to increase patient satisfaction can be pursued in various ways including by improving the quality of service. A service is said to be satisfied by the patient if the service provided is in accordance with expectations and does not cause dissatisfaction. In this study aims to determine how much influence the quality of service on patient satisfaction. This type of research is quantitative with a cross-sectional design. The technique used in this study is probability sampling with an accidental sampling approach with a total of 93 respondents. It is known that simple linear regression analysis in this study is obtained. Based on the results of the research, the simple linear regression equation is obtained as follows Y = 3.854 + 0.092 X calculated t value of 2.119. at Degree of Freedom (df) = n-2, df = 93-2 = 91, then a t table of 1,984 is found. Then it can be seen that t count > t table (2.119> 1.984). So it can be concluded that Service Quality (X) can have a positive effect on patient satisfaction (Y).